PERLINDUNGAN HUKUM BAGI PENCIPTA KARYA SENI TERHADAP PELANGGARAN HAK CIPTA MELALUI NFT - Hambarsika, Gusti Ayu Ketut Astri Meitasari; Dian Sawitri, Dewa Ayu (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 07 (2024), 2025)
The aims of this study is to find out the legal protection for creators of works of art against copyright infringement through NFT and to find out the consequences of buying NFT that violate copyrights. The normative legal research method with a statutory approach is used in writing this study. The results of the study show that creators of works of art can utilize Digital Rights Management (DRM) and policies on the NFT marketplace as preventive protection, as well as alternative dispute resolution or through the courts by filing civil lawsuits or criminal charges according to what has been regulated in the Copyright Act as repressive protection against copyright infringement through NFT. The consequence of buying NFT that violate the copyright of the buyer will suffer losses because NFT from copyright infringement can be removed and the seller must be responsible for compensating losses arising from the goods traded, if referring to the provisions of the Consumer Protection Act.